2007
DOI: 10.1016/j.ecresq.2007.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Preschoolers’ academic readiness: What role does the teacher–child relationship play?

Abstract: We examined the role of the teacher-child relationship quality (close, dependent, and conflictive) on preschoolers' (N = 95) academic readiness for kindergarten, and we tested children's prosocial and aggressive behavior and peer group exclusion as mediators of this relation. A unique feature of this study is the ethnically and socio-economically diverse preschool-aged sample. The association between close teacher-child relationships and academic readiness was partially mediated by prosocial behavior and peer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
108
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(119 citation statements)
references
References 45 publications
7
108
1
3
Order By: Relevance
“…These studies found that dependency is concurrently associated with less classroom engagement, more emotional problems, more conduct problems, more social withdrawal, and more peer problems (Birch & Ladd, 1997;Howes, Hamilton, & Matheson, 1994;Koomen et al, 2012;Palermo, Hanish, Martin, Fabes, & Reiser, 2007). Doumen and colleagues (2012), for example, found that children's average level of dependency on the teacher ©American Psychological Association, 2017.…”
Section: Dependency In Teacher-child Relationshipsmentioning
confidence: 99%
“…These studies found that dependency is concurrently associated with less classroom engagement, more emotional problems, more conduct problems, more social withdrawal, and more peer problems (Birch & Ladd, 1997;Howes, Hamilton, & Matheson, 1994;Koomen et al, 2012;Palermo, Hanish, Martin, Fabes, & Reiser, 2007). Doumen and colleagues (2012), for example, found that children's average level of dependency on the teacher ©American Psychological Association, 2017.…”
Section: Dependency In Teacher-child Relationshipsmentioning
confidence: 99%
“…The teacher-pupil relationship is important, particularly in early childhood (Palermo, Hanish, Martin, Fabes, & Reiser, 2007) and, in general, because of its effects on the child's psychological well-being and social adaptation (Birch & Ladd, 1997;Baker, Grant, & Morlock, 2008;Koomen et al, 2012); for this reason, it is fundamental to have available an instrument that can be used to assess the relationship itself. The STRS, given its validity, can be a serviceable questionnaire for studying such a construct, both as a monitoring scale of a given relationship and as a way to help teachers achieve a better level of awareness of their educational skills.…”
Section: Discussionmentioning
confidence: 99%
“…In several other research studies which examined the relationships of students with and without SN to their teachers, it was also suggested that the social skills and problem behaviors of students impact these relationships (Birch & Ladd, 1998;Blacher et al, 2009;Doumen et al, 2008;Eisenhower et al, 2007;Hughes et al, 1999;Palermo et al, 2007). Studies which examined the relationships of students without SN to their teachers suggested that students who have more problem behaviors have more conflicts with their teachers, and students who have better social skills have closer relationships with their teachers (Birch & Ladd, 1998;Hamre et al, 2007;Palermo et al, 2007;Pianta & Nimetz, 1991;Pianta et al, 1995). Studies which examined the relationships of students with SN to their teachers also showed similar results (Blacher et al, 2009;Eisenhower et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In order to create both a positive classroom environment and form positive student-teacher relationships, the importance of teacher characteristics as well as student characteristics might be emphasized. Student characteristics, especially problem behaviors, are very important for student-teacher relationships (Doumen et al, 2008;Howes, 2000;Palermo et al, 2007). Problem behaviors are defined as behaviors which prevent a student from effectively functioning in the classroom and endangers both their safety and their peers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation